2016
DOI: 10.15376/biores.11.4.8457-8469
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Allyl-Functionalized Deep Eutectic Solvent to Promote Dissolution of Cellulose

Abstract: Deep eutectic solvents (DESs) offer attractive options for the "green" dissolution of cellulose. However, the protic hydroxyl group causes weak dissolving ability of DESs, requiring the substitution of hydroxyl groups in the cation. In this study, a novel allyl-functionalized DES was synthesized and characterized, and its possible effect on improved dissolution of cellulose was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…DESs composed of [Ch]Cl:im (3:7), [Ch]Cl:U (1:2) and [Na111]Cl:oxalic acid (1:1) are able to dissolve cotton linter pulp [ 189 ]. The imidazole-based DESs presented the highest cellulose solubility, which can be attributed to their strong hydrogen bond acceptor character.…”
Section: Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…DESs composed of [Ch]Cl:im (3:7), [Ch]Cl:U (1:2) and [Na111]Cl:oxalic acid (1:1) are able to dissolve cotton linter pulp [ 189 ]. The imidazole-based DESs presented the highest cellulose solubility, which can be attributed to their strong hydrogen bond acceptor character.…”
Section: Cellulosementioning
confidence: 99%
“…This in turn allows a more effective interaction with DESs components through hydrogen bonding with the PEG hydrophilic part (hydroxyl groups). Therefore, the addition of PEG made cellulose more hydrophilic [ 189 ]. As a complementary study, allyl-functionalized DESs also demonstrated the ability to dissolve cellulose, leading to a maximum solubility of 6.48 wt% at 110 °C [ 190 ].…”
Section: Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…As deep eutectic solvents (DES) and ILs have been reported to be good solvents for cellulose, they have also been tested for their plasticizing efficiency in cellulose films. A typical DES, choline chloride and urea, has been suggested to function as an effective plasticizer, showing no phase separation and leading to transparent, soft materials having enhanced elongation.…”
Section: Lignocellulosic Biomassmentioning
confidence: 99%
“…Up to 6.5 wt % cotton linters was soluble in a mixture of allyltriethylammonium chloride and oxalic acid at 110 °C after 2 h [ 228 ], which is one of the highest values reported for DES. Only 2.5 wt % was soluble in ChCl/imidazole [ 229 ].…”
Section: Applications Of Qaes For Cellulose Dissolution Shaping Amentioning
confidence: 99%